Volumetric alterations in auditory and visual subcortical nuclei following perinatal deafness in felines - Alessandra Sacco; Stephen G. Gordon; Stephen G. Lomber (NeuroImage)
In response to sensory deprivation, the brain adapts to efficiently navigate a modified perceptual environment through a process referred to as compensatory crossmodal plasticity, allowing the remaining senses to repurpose deprived regions and networks. A mechanism that has been proposed to contribute to this plasticity involves adaptations within subcortical nuclei that trigger cascading effects throughout the brain. The current study uses 7T MRI to investigate the effect of perinatal deafness on the volumes of subcortical structures in felines, focusing on key sensory nuclei within the brainstem and thalamus. Using both ROI-based and morphometric approaches, the regional macrostructure of four auditory and two visual nuclei were studied, as well as the corresponding volumetric asymmetries within and across groups. In the auditory pathway, significant bilateral volumetric reductions were revealed within the lower-level structures (cochlear nucleus, superior olivary complex, and inferior colliculus), alongside a shrinkage of solely the left medial geniculate body. Within the visual pathway, a significant bilateral volumetric reduction was found in the lateral geniculate nucleus, with the superior colliculus largely unaffected. These regional alterations, along with an extensive loss of volume throughout the brainstem of deprived cats, were attributed to disuse-driven atrophy corresponding to evolved functional demands reflective of a modified perceptual environment. Furthermore, the left-right volumetric symmetries of the control subcortex were preserved following deafness. Overall, the current study reinforces the notion that subcortical structures likely contribute to compensatory crossmodal plasticity prior to cortical processing, and that these deafness-induced adaptations appear to be influenced by both the level of the affected structure within its respective sensory processing hierarchy and the specifics of its afferent profile.